Culturomics and Circular Agronomy: Two Sides of the Same Coin for the Design of a Tailored Biofertilizer for the Semi-Halophyte Mesembryanthemum crystallinum - Eloísa Pajuelo; Noris J. Flores-Duarte; Salvadora Navarro-Torre; Ignacio D. Rodríguez-Llorente; Enrique Mateos-Naranjo; Susana Redondo-Gómez; José A. Carrasco López (Plants, 2023)
According to the EU, the global consumption of biomass, fossil fuels, metals, and minerals is expected to double by 2050, while waste will increase by 70%. In this context, the Circular Economy Action Plan (CEAP) intends to integrate development and sustainability. In this regard, tailored biofertilizers based on plant growth-promoting bacteria (PGPB) can improve plant yield with fewer inputs. In our project, an autochthonous halophyte of the Andalusian marshes, namely Mesembryanthemum crystallinum, was selected for its interest as a source of pharmaceuticals and nutraceuticals. The aim of this work was to use a culturomics approach for the isolation of specific PGPB and endophytes able to promote plant growth and, eventually, modulate the metabolome of the plant. For this purpose, a specific culture medium based on M. crystallinum biomass, called Mesem Agar (MA), was elaborated. Bacteria of three compartments (rhizosphere soil, root endophytes, and shoot endophytes) were isolated on standard tryptone soy agar (TSA) and MA in order to obtain two independent collections. A higher number of bacteria were isolated on TSA than in MA (47 vs. 37). All the bacteria were identified, and although some of them were isolated in both media (Pseudomonas, Bacillus, Priestia, Rosellomorea, etc.), either medium allowed the isolation of specific members of the M. crystallinum microbiome such as Leclercia, Curtobacterium, Pantoea, Lysinibacillus, Mesobacillus, Glutamicibacter, etc. Plant growth-promoting properties and extracellular degrading activities of all the strains were determined, and distinct patterns were found in both media. The three best bacteria of each collection were selected in order to produce two different consortia, whose effects on seed germination, root colonization, plant growth and physiology, and metabolomics were analyzed. Additionally, the results of the plant metabolome revealed a differential accumulation of several primary and secondary metabolites with pharmaceutical properties. Overall, the results demonstrated the feasibility of using “low cost media” based on plant biomass to carry out a culturomics approach in order to isolate the most suitable bacteria for biofertilizers. In this way, a circular model is established in which bacteria help plants to grow, and, in turn, a medium based on plant wastes supports bacterial growth at low prices, which is the reason why this approach can be considered within the model of “circular agronomy”.